Plant Extracts as Natural Insecticides: A Study on Bean and Maize Weevils - O. O. Ogunsina; M. O. Oladimeji; L. Lajide (African Journal of Environmental Economics and Management, 2024)
A study was conducted to evaluate the insecticidal action of hexane extracts of three locally available plants namely: Lantana camara (Verbenaceae), African nutmeg [Monodora myristica (Gaerth) Dunal] and Enuopiri [Euphorbia lateriflora, Schum and Thonner] against bean weevil Callosobruchus maculatus (F.) and maize weevil, Sitophilus zeamais) Motsch with response to the insect mortality. Results revealed that all test materials exhibited mortality action against bean weevil and maize weevil. African nutmeg extracts had greater mortality action against both the beans weevil (100%) and maize weevil (96%) after 24 h of treatment. Lantana extracts were observed to have moderate mortality effect; bean weevil (93%) and maize weevil (73.3%) while Enuopiri had average mortality effect; bean weevil (46.7%) and maize weevil (50%) all with extract concentration of 10 g/100 ml (extract/solvent). The overall results showed that bean weevil was much more susceptible to all the extracts than maize weevil, having recorded the height mortality rate.